(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
In this article, the essence, goals, objectives of health-improving technologies in modern conditions and the relevance and importance of health-improving technologies in physical education and sports are scientifically substantiated by its functions of physical health-improving in the formation of a healthy lifestyle today, international experiments.